Algoritma Naïve Bayes untuk Rekomendasi Seleksi Peserta Paskibraka Berbasis Website - Mohamad Nurizki; Winda Apriandari; Asriyanik Asriyanik (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
In the series of intensive Paskibraka activies, each individual strives to build strong character. Paskibraka serves as a means to cultivate a sense of love for the homeland. Every year, on the commemoration of the raising ceremony is conducted on August 17th. One important part of the ceremony is the hosting of the red and white flag by Paskibraka member. PASKIBRAKA (Flag Raising Troop) represent the selected new generation of Indonesia through a selection process participated by student from various high school. The PASKIBRAKA selection involves several stages, and to facilitate the selection process, a guideline for activities has been formulated in the Minister of Youth and Sports Regulation (Permenpora) No. 0065 of 2015. The classification appiled utilizes the Naïve Bayes algorithm with the Knowladge Discovery in Databases (KDD) method. The naïve bayes algorithm is a data mining and statistical classification algorithm that applies Bayes’theorem under the assumption of independence between variables. The advantages of the naïve bayes algorithm lie in its scability in handing the number of predictors and data points, its ability to make probability prediction, and its capability to handle both continuous and discrate data. The result of this research have achieved the from of automated classification of the eligibility of Paskibraka participant selection, data mining whether the are aligible or not to become members of Paskibraka in Sukabumi Regency.